Socio-economic status of buffalo farmers and management practices of buffaloes in selected areas of Jamalpur district in Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2020)
A field survey was conducted to investigate the farmers’ socio-economic status and management practices of buffaloes along with profitability analysis of buffalo rearing at Madargonj upazila of Jamalpur district. The data were collected during October to December 2018 from 60 buffalo keepers randomly selected from four unions of Madargonj upazila through pre-tested and pre-designed interview schedule. Buffalo rearing was practiced by the middle (30-40 years) aged farmers (51.7%) and almost three fourth of the farmers were illiterate. Buffalo keepers (40%) had medium sized family and belonged to small category of farmers (50%). Farmers usually purchased one pair of buffaloes and reared for 2 years but they (86.7%) reared buffaloes as their family heritage without any training. Majority of the farmers reared crossbred buffaloes having herd size of 4-10 buffaloes. Buffalo houses were constructed by straw (63.4%), tin (28.3%) and only 8.3% half building. Buffaloes were fed usually with locally available river side grasses and concentrate feeding was not found in majority of cases (75%). Natural service was the major practice for breeding of their buffaloes. The most prevalent disease is foot and mouth disease although buffaloes were affected by others. Most of the farmers (66.7%) performed wallowing of their buffaloes once a day. Yearly expenditure, gross income and net income were Tk. 9570, Tk. 26400 and Tk. 16830; respectively indicating that buffalo rearing is highly profitable in Madargonj. The annual food and cloth purchasing capacity of the buffalo farmers were found to be increased to 65.60 and 57.24%, respectively along with other parameters. The findings of this study clearly indicated that socio-economic profile of buffalo farmers was improved through buffalo rearing although the management practices need to be improved with scientific approaches.Asian Australas. J. Food Saf. Secur. 2020, 4 (2), 49-52